Implementing a Care Pathway for small and nutritionally at‐risk infants under six months of age: A multi‐country stakeholder consultation - Tabitha D. vanImmerzeel; Maty Diagne; Indou Deme/Ly; Amanda E. Murungi; Saliou Diouf; Marko Kerac; Carlos S. Grijalva‐Eternod; Louise T. Day (Wiley, 2023)
Abstract Nutritional vulnerability under the age of 6 months is prevalent in low‐ and middle‐income countries with 20.1% infants underweight, 21.3% wasted and 17.6% stunted in a recent review. A novel Care Pathway for improved management of small and nutritionally at‐risk infants under 6 months and their mothers (MAMI) has recently been developed to provide outpatient care at large coverage. We aimed to investigate stakeholders' views on the feasibility of its implementation and to identify barriers and enablers. This was an early stage formative mixed‐methods study: an online survey plus in‐depth interviews with country‐level stakeholders in nutrition and child health from different geographical regions and stakeholder groups. 189 stakeholders from 42 countries responded to the online survey and 14 remote interviews were conducted. Participants expressed an urgent need for improved detection and care for small and nutritionally at‐risk infants under 6 months. Whilst they considered the MAMI Care Pathway feasible and relevant, they noted it was largely unknown in their country. The most mentioned implementation barriers were: community‐specific needs and health care seeking barriers, health workers' lack of competence in breastfeeding counselling and the absence of a validated anthropometric screening method. Possible enablers for its implementation were: patients' preference for outpatient care, integrating the MAMI care pathway into existing maternal and child health programmes and the possibility of a local pilot project. Adaptation to the local context was considered crucial in further scale‐up.